Psychometric validation of Arabic attention control scale: reliability, correlation, PCA, and CFA analyses - Khadraoui, Amine; Barebzi, Abdellah (International Journal of Evaluation and Research in Education (IJERE), 2025)
The scarcity of reliable tools to measure attention control among Arabic speaking learners represents a key research problem. To address this gap, this study aimed to develop and evaluate the Arabic version of the attention control scale (ACS). The research was conducted on a sample of (N=210) Moroccan students in their second year of middle school (2023/2024), using precise translation methods, including “forward and backward translation”. The reliability of the scale was confirmed through Cronbach’s alpha (α=0.832), McDonald’s omega (Ʊ=0.820), and split-half reliability (ρ=0.870). The factor structure of the scale was verified using principal component analysis (PCA), while confirmatory factor analysis (CFA) confirmed the model’s goodness of fit (χ²=1689.398, df=66, *p<.001; Kaiser-Meyer-Olkin (KMO)=0.672). The results showed statistically significant correlations between the scale’s dimensions: general attention control (GA), attention focusing (AF), and attention shifting (AS) (*p<.001). The findings confirmed that the 12 item Arabic version of the ACS (short version) has strong psychometric properties with factor loadings ranging from 0.311 to 0.825. This study is considered an important step in developing attention assessment tools for learners in the Arab educational context. It provides a standardized scale to measure the attention process, which helps enable teachers to accurately diagnose attention difficulties and provide targeted educational interventions. These interventions contribute to improving learners’ focus and engagement, thereby enhancing the overall effectiveness of the educational process.